2017
DOI: 10.4172/2576-1471.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptors: Structure, Function, Signaling and Clinical Applications

Abstract: Angiotensinogen -a serpin family protein predominantly produced by the liver is systematically processed by proteases of the Renin Angiotensin system (RAS) generating hormone peptides. Specific cell surface receptors for at least three distinct angiotensin peptides produce distinct cellular signals that regulate system-wide physiological response to RAS. Two well characterized receptors are angiotensin type 1 receptor (AT1 receptor) and type 2 receptor (AT2 receptor).They respond to the octapeptide hormone ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Furthermore, ACEIs do not interfere with the conversion of angiotensin-I to angiotensin-1-9 because they are converted by endopeptidases. After conversion to angiotensin-1-9, it is cleaved by ACE-2, which seems unaffected by classical ACEI, to become angiotensin-1-7, which binds to MAS receptors, causing the opposite effect of AT1R (vasodilatation, apoptosis, antiproliferation) (62)(63)(64)(65)(66). Currently, there are many ACEIs in existence in addition to captopril: enalapril, benazepril, and fosinopril and others.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Furthermore, ACEIs do not interfere with the conversion of angiotensin-I to angiotensin-1-9 because they are converted by endopeptidases. After conversion to angiotensin-1-9, it is cleaved by ACE-2, which seems unaffected by classical ACEI, to become angiotensin-1-7, which binds to MAS receptors, causing the opposite effect of AT1R (vasodilatation, apoptosis, antiproliferation) (62)(63)(64)(65)(66). Currently, there are many ACEIs in existence in addition to captopril: enalapril, benazepril, and fosinopril and others.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…When Ang (1–7) binds to MAS receptors, it causes vasodilation, natriuresis, diuresis, and also exerts anti-proliferative and anti-inflammatory effects. This arm of the pathway constitutes the so-called “protective pathway” of the RAS as the effects are believed to be physiologically favourable [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The RAS appears to be important in a number of pathological processes. AngII/AT1 activation leads to a number of unfavorable effects, which include vasoconstriction and hypertension, cellular differentiation and growth, endothelial dysfunction, and the formation of reactive oxidative species (ROS) that may ultimately lead to organ damage [2] , [3] , [4] . The vasodilator nitric oxide (NO) is released when Ang (1–7) binds to MAS and AT2 receptors [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest, SARS-CoV-2 interacts with the RAS via ACE2, which was also identified as a functional receptor for Severe Acute Respiratory Syndrome CoronaVirus (SARS-CoV) ( 7 9 ). It has been indicated that RAS activation during SARS-CoV-2 infection leads to a number of unfavorable effects, which include vasoconstriction and hypertension, cellular differentiation and growth, endothelial dysfunction, and the formation of Reactive Oxidative Species (ROS) that may ultimately lead to organ damage ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%